Diplomasi Politik Kesultanan Palembang Dan Kolonial Belanda Tanggal 23 Mei 1803 - Muhammad Ilham (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
Abstract Diplomacy, Politics, Sultanate, Colonial This research was conducted as an effort to find out how the political diplomacy relations used by the Palembang sultan in establishing relations with Western powers, especially the Dutch Company in the archipelago. Political diplomacy is important because diplomacy is one way to foster and establish friendly relations between one person and people from other countries who aim to collaborate in various interests of the sultanate and government interests. To be able to establish relationships with one another, a device or diplomat is needed to establish the relationship. The main problem discussed in this study is to look at the Codicology, Philology, Transliteration, and Types of diplomacy in the Malay letters made by the Palembang authorities for the Dutch colonial government and also this research aims to find out what reasons and objectives to be achieved in fill in the letters. For this purpose, this type of research includes qualitative research, using secondary and primary sources. Primary sources are obtained from original texts and secondary sources in the form of books relating to the Palembang Sultanate, theses, dissertations and scientific journals. The technique of collecting data is to examine and select selectively then displayed and used in accordance with the time limit, namely the 19th century. After that, the data analysis technique uses descriptive-analytical techniques, namely to describe the full text, then analyze the meanings contained in the method and methods used is a single diplomatic edition method. After that, the writing of history to see and describe the findings in the letter with a historical approach. Keywords: Diplomacy, Politics, Sultanate, Colonial